2009
DOI: 10.1515/cclm.2009.221
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of serum antioxidant micronutrients and sociodemographic factors to cervical neoplasia: a case-control study

Abstract: Background: Although there have been some epidemiological studies on the effects of diet and nutritional status on cervical carcinogenesis, evidence for a protective effect of antioxidant micronutrients against cervical neoplasia is insufficient. The relationship between serum antioxidant micronutrients and sociodemographic factors and the risk of cervical neoplasia was investigated in this multi-center, case-control study. Methods: The study population included women with histopathological diagnosis of cervic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…Epidemiological studies showed that high intake and high blood levels of zeaxanthin (alone or combined with lutein) might be associated with a lower risk of occurrence of various malignant tumors, including non-Hodgkin lymphoma [22, 23], cervical [2428], esophagus [2931], stomach [31, 32], lung [3335], breast [34, 3638, 42], kidney [39], head and neck [40], colon [41, 43] and pancreas [31, 44], cancers. …”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies showed that high intake and high blood levels of zeaxanthin (alone or combined with lutein) might be associated with a lower risk of occurrence of various malignant tumors, including non-Hodgkin lymphoma [22, 23], cervical [2428], esophagus [2931], stomach [31, 32], lung [3335], breast [34, 3638, 42], kidney [39], head and neck [40], colon [41, 43] and pancreas [31, 44], cancers. …”
Section: Discussionmentioning
confidence: 99%
“…For ever-smoking, 105 studies were initially identified, but many of them were excluded in the final analysis for several reasons: risk estimates with precision information (e.g., standard error, 95% confidence interval [CI]) were not available, the classification for smoking was different than never, former, and current smokers (53 studies), and multiple results were reported from the same study population (13 studies). Nineteen studies were used in the final analysis to estimate the pooled RRs for ever-smoking and the RRs for most cancer sites were estimated from a few studies including a large-scale cohort study [18-36]. When possible, the pooled RRs were separately estimated for cancer incidence and mortality.…”
Section: Methodsmentioning
confidence: 99%
“…There was no randomized controlled trial (RCT) or cohort study included in our meta-analysis based on the criteria. All the ORs in the 15 studies were estimated based on the highest compared with the lowest dietary vitamin E intake or blood levels of vitamin E. Of those studies, 9 studies were conducted in America [ 6 , 10 , 13 16 , 18 , 22 , 23 ], 5 in Asian populations [ 11 12 , 17 , 19 , 21 ], 1 study in Europe [ 20 ]. All the studies were adjusted for a wide range of potential confounders, such as age, education, parity, and HPV infection status.…”
Section: Resultsmentioning
confidence: 99%